2018
DOI: 10.3390/ijms19113612
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Self-Incompatibility Alleles by Specific PCR Analysis and S-RNase Sequencing in Apricot

Abstract: Self-incompatibility (SI) is one of the most efficient mechanisms to promote out-crossing in plants. However, SI could be a problem for fruit production. An example is apricot (Prunus armeniaca), in which, as in other species of the Rosaceae, SI is determined by an S-RNase-based-Gametophytic Self-Incompatibility (GSI) system. Incompatibility relationships between cultivars can be established by an S-allele genotyping PCR strategy. Until recently, most of the traditional European apricot cultivars were self-com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 61 publications
1
17
1
Order By: Relevance
“…According to 46 self-compatible genotypes, considering the proportion of regional samples, the highest proportion (40%) with 13 genotype out of 32 was assigned to the Marmara region and the lowest percentage with 3 genotypes out of 24 (12% of the region samples) allocated to the Central Anatolian region so, more attention should be paid to contrivances, regarding commercial production and orchard design in this region. The results confirmed that the self-incompatibility feature tends to increase in the species, which is contrary to the former reports that most cultivars were compatible (Mehlenbacher et al 1991;Herrera et al 2018).…”
Section: Identification Of Alleles and Compatibilitysupporting
confidence: 76%
See 1 more Smart Citation
“…According to 46 self-compatible genotypes, considering the proportion of regional samples, the highest proportion (40%) with 13 genotype out of 32 was assigned to the Marmara region and the lowest percentage with 3 genotypes out of 24 (12% of the region samples) allocated to the Central Anatolian region so, more attention should be paid to contrivances, regarding commercial production and orchard design in this region. The results confirmed that the self-incompatibility feature tends to increase in the species, which is contrary to the former reports that most cultivars were compatible (Mehlenbacher et al 1991;Herrera et al 2018).…”
Section: Identification Of Alleles and Compatibilitysupporting
confidence: 76%
“…It should be noted that standardization of the S-alleles identification criteria is essential in various laboratories, including the full sequencing of S alleles and utilization of the identic primer pairs. This will lead to easy S-allele identification without confusion and will provide valuable information for pear breeders (Herrera et al 2018). Obtained results in this study make it possible to organize the incompatibility relationships between pear genotypes with former unknown pollination knowledge and provide the possibility to select suitable parents in designing new crosses in pear production and breeding programs.…”
Section: Discussionmentioning
confidence: 83%
“…The DNA sequence encoding this hexapeptide has frequently been used for the development of consensus primers for PCR-based S-genotyping (DeFranceschi et al., 2012). S-RNase genotyping by PCR is commonly used in Rosaceae species to determine incompatibility relations between cultivars, often in combination with field-controlled pollination assays (Zuccherelli et al., 2002; Larsen et al., 2016; Herrera et al., 2018). Figure 3 displays a schematic representation of the protein sequence of the S-RNase of Pyrus, Prunus , and Solanaceae.…”
Section: The Genetic Control Of Gsi In Pyrusmentioning
confidence: 99%
“…In these crosses, pollen tube growth stops somewhere along the style length and practically no pollen tubes can be observed at the base [22,23]. Self-incompatibility is one of the most efficient mechanisms to promote out-crossing in plants but could be a problem for fruit production [24]. So far, 19 S-RNase alleles have been cloned and sequenced for European pear, which can be used to characterize more than 130 cultivars [25].…”
Section: Introductionmentioning
confidence: 99%